OS MODAIS "DEVERâ€? E "PODERâ€? E O USO DE VERBOS NA FORMA IMPERATIVA NA CONSTRUÇÃO DA ARGUMENTAÇÃO DA CAMPANHA "AMIGOS DA ESCOLAâ€? (Letras & Letras, 2007)
ABSTRACT: This work is aimed at showing the importance of the modals "canâ€? and "mayâ€? and the use of verbs in the imperative form for the construction of a textÂ´s argumentation. The text in analysis was retired of the material to divulgation of the Project "Amigos da Escolaâ€?.